Mechanical properties of concrete composites subject to elevated temperature - Novak, Josef; Kohoutkova, Alena (Fire safety journal, 2018)
Fire resistance represents an important parameter which is necessary to consider during the structural design of buildings. It is defined as an ability of building components to perform their intended load-bearing functions under fire exposure. In terms of fire resistance, the right choice of a construction material plays a key role and can reduce structural damage or even save human lives. The building industry offers a wide range of materials whose structural behaviour is more or less affected by temperature. Recently, concrete has become one of the most utilized materials used for a various kind of buildings. While the knowledge and experience with concrete behaviour under ambient temperature are well-known, the behaviour under elevated temperature has to be deeply investigated. The paper deals with observing the behaviour of concrete composites with addition of fibres under ambient and elevated temperature with the aim to determine the mechanical properties of materials. The experimental tests were conducted on three selected concrete composites which differ in a type and content of fibrous reinforcement used. The experimental work carried out was divided into several phases. First of all it was necessary to leave the produced specimens aging and drying in order to minimize the risk of unexpected damage caused by concrete spalling during heating. Time to time, the specimens were weighted with the aim to determine the loss of weight imposed by drying. Then, a heat transport test was performed on a few reference specimens in order to determine the time required for uniform heating the specimens up to 200 °C, 400 °C and 600 °C. In the last phase, conventional testing methods were undertaken to determine the mechanical properties of concrete composites at ambient and elevated temperature. A compression test and a splitting tensile test were conducted on 150 mm cubes. Based on the results, the peak and residual strength of the materials were determined for various temperature levels. The obtained findings contribute to improving the knowledge in the field of both concrete structures exposed to high temperature and structural behaviour of fibre reinforced concrete. The findings can be also utilized in case of the structural design of concrete structures with the high risk of fire loading. [Display omitted]